Effects of neuroticism on pre-exam irritable bowel syndrome in female middle school students: mediating role of intolerance of uncertainty and moderating role of exercise duration - Wu, Hou; Liu, Qiqin; Liu, Jianping; Liu, Mingfan (Frontiers in Psychiatry, 2024)
Background China, which is deeply influenced by Confucianism, places special emphasis on students’ test scores. Previous studies have shown that neuroticism is associated with irritable bowel syndrome (IBS) in adolescents. However, the mechanisms underlying this association before exams in female secondary school students are unknown. The present study sought to ascertain whether IU mediates the association between neuroticism and pre-exam IBS, and to determine whether exercise duration moderates the relationship between neuroticism and pre-exam IBS. Methods The sample consisted of 685 Chinese female middle school students (Mage = 14.81, SD = 1.55, range = 11-18) who completed paper questionnaires, including the neuroticism subscale of the Chinese Neuroticism Extraversion Openness Five-Factor Inventory, the IBS Symptom Severity Scale, a simplified version of the Intolerance of Uncertainty Scale, and a movement time questionnaire. Independent samples t-test was used to compare differences between groups and Pearson correlation coefficient was used to investigate the bivariate correlation. The SPSS PROCESS 4.1 plug-in was then used to examine the mediating role of IU as well as the moderating role of movement time between neuroticism and pre-exam IBS. Results Neuroticism and IU were significantly correlated with pre-exam IBS (r = 0.39, 0.30, respectively; all p < 0.01), and neuroticism was significantly correlated with IU (r = 0.46, p < 0.01). Neuroticism had a direct predictive effect on pre-exam IBS in Chinese female middle school students (β = 0.32, p < 0.001), and IU also had a positive effect on pre-exam IBS (β = 0.15, p < 0.001). The mediating effect value of IU on the total effect was 18.09%. The relationship between neuroticism and pre-exam IBS was moderated by movement time (β = -0.23, p < 0.05). Conclusion IU plays a mediating role between neuroticism and pre-exam IBS, and exercise time plays a moderating role between neuroticism and pre-exam IBS. These findings provide an evidence for neuroticism intervention, IU management, and pre-exam IBS improvement in female middle school students.